Vulnerability of Teenagers to sects’ recruitment - Hernández Prados, Mª Ángeles (2017)
The uniqueness» fracture of the ruling speech about modernity has plunged usinto despair of relativity voices of postmodernism. We assist, according to Garcia(2008), to a new era characterized by the implementation of a spiritual market anda religions cocktail. The increased sensitivity of citizenship by cultivating integrityalong with the host institutions crisis exacerbates the vulnerability of people tobe influenced of sectarian ideologies. After having analyzed society as a beneficialcrop to the sects, the speech focused on adolescence as the most vulnerable stage,claiming that education, from many different contexts, is the most likely responseto prevent the sect»s recruitment.